2001
DOI: 10.1253/jcj.65.257
|View full text |Cite
|
Sign up to set email alerts
|

Triple Valve Replacement With Bileaflet Mechanical Valves

Abstract: ecause the outcome of tricuspid valve replacement (TVR) is relatively poor, most tricuspid valve surgery is repair procedures. As a result, the experience of prosthetic valve replacement in the tricuspid position is limited and the optimal choice of replacement valve is still controversial. Generally, bioprostheses have excellent antithrombogenic characteristics with relatively greater durability, and many recommend this choice for TVR. 1-3 On the other hand, satisfactory results with the newly developed bilea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(16 reference statements)
0
2
0
Order By: Relevance
“… 12 Kawano and his colleagues published a retrospective study and reported that after TVR six out of nineteen SJM valves have been detected with thrombosis of valve (2.9%/patient-years), and they reported the tricuspid valve position vulnerable to thrombosis. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Kawano and his colleagues published a retrospective study and reported that after TVR six out of nineteen SJM valves have been detected with thrombosis of valve (2.9%/patient-years), and they reported the tricuspid valve position vulnerable to thrombosis. 13 …”
Section: Discussionmentioning
confidence: 99%
“…12 Kawano and his colleagues published a retrospective study and reported that after TVR six out of nineteen SJM valves have been detected with thrombosis of valve (2.9%/patient-years), and they reported the tricuspid valve position vulnerable to thrombosis. 13 Better bio prostheses are a good choice for lowpressure chamber (as right sided is low pressure area|) than the high pressure chamber (left sided in the mitral and aortic position). 14 Stenosis, dysfunction and late valve calcification are the complications of bio prostheses.…”
Section: Discussionmentioning
confidence: 99%